New host species for Leptospira borgpetersenii and Leptospira interrogans serovar Copenhageni - Colombo, Valeria Carolina; Gamietea, Ignacio José; Grune Loffler, Sylvia; Brihuega, Bibiana Felicitas; Beldomenico, Pablo Martín (Elsevier, 2019)
We investigated the presence of infection by Leptospira spp. in an assembly of Sigmodontinae rodents from the Paraná Delta, Argentina. Rodents were captured in places with natural grassland, implanted forest, with and without raising cattle and in sites prone and not prone to flooding. The DNA was amplified from cultured isolates by PCR and Leptospira spp. strains were genotyped using Multiple – Locus Variable Number Tandem Repeat Analysis (MLVA). We isolated Leptospira interrogans serovar Copenhageni from Oligoryzomys nigripes, Leptospira borgpetersenii from Scapteromys aquaticus and Leptospira interrogans serovar Icterohaemorrhagiae from Akodon azarae. The zoonotic Leptospira isolated and genotyped from O. nigripes and S. aquaticus are the first reports from these species. The geographic range of these rodent species include, in addition to Argentina, the countries of Paraguay, Uruguay and Brazil, suggesting that these rodents might be involved in the transmission of spirochetes in other regions. Human and animal health care professionals should be alert to the potential occurrence of leptospirosis in areas where these rodent species are present.